Optimalisasi Peran PPAT Dalam Pencegahan Praktik Mafia Tanah: Analisis Yuridis Atas Fungsi Pengawasan Dan Akuntabilitas Jabatan - Mahendra, Martins Izha; Djaja, Benny; M Sudirman, M Sudirman (Equality : Jurnal Hukum dan Keadilan, 2025)
The Land Deed Official (PPAT) holds a strategic role in Indonesia’s land law system, as they are authorized to draw up authentic deeds that serve as the legal basis for the transfer of land rights. The legal status of PPAT is regulated under the Basic Agrarian Law, Government Regulation No. 24 of 1997, and Government Regulation No. 37 of 1998 in conjunction with Government Regulation No. 24 of 2016. However, in practice, problems arise regarding the involvement or negligence of PPAT in land mafia activities due to weak supervision and lack of professional integrity. This raises the question of how effectively PPAT’s responsibility and accountability function in preventing land-related crimes. This study aims to analyze the role, authority, and supervisory mechanisms of PPAT in preventing land mafia practices in Indonesia. The research employs a normative legal method with statutory and conceptual approaches, supported by qualitative analysis of primary and secondary legal materials. The findings show that the effectiveness of PPAT’s role is highly influenced by consistent supervision from the Ministry of Agrarian Affairs/National Land Agency (ATR/BPN), strict enforcement of administrative and criminal sanctions, and the implementation of digital land administration systems. Strengthening PPAT integrity is essential to ensure legal certainty and enhance public trust in Indonesia’s land law system.